Evaluación comparativa durante la fermentación en la elaboración de vino de uva de borgoña negra (vitis labrusca) Usando cepa pura (Saccharomyces cereviciae) y pie de cuba (Saccharonmyces Spp) - Ramirez Trigozo, Edson (2000)
The present paper is oriented to elaborate wine using, pure vine stock (Saccharomyces cereviciae variety ellipsoideus) and cube foot (Saccharomyces Spp), evaluate and compare the clarified by means of use biopectinasa and white of egg, in grape juice variety black burgundy (Vitis labrusca). The comparison to themselves on fermentation velocity, using different levels of pure vine stock and cube foot in standardized grape juice 25% SS and 3.5 pH; determined by formation of alcohol and a sensorial analysis applying Durbin non -parametric test 5% probability, did result as a better fermentation treatment using cube foot to 10% daring 5 days with average temperature 30ºC. The clarified test on elaborated wine to cube foot 10%, using biopectinasa through a sensorial evaluation (affective test) and analysis of variance (ANVA) to 5% significance, statistically not exist significant difference among clarifying -samples using (0.01 %, 0.02%, 0.03%), and compared with white of egg (0.7g/I) in terms of wine dazzle, did result biopectinasa 0.02% as a better clarifying - sample. Recommended flow for elaborating wine starting grape variety black burgundy Natis labrusca) is: reaped grape to 130 days after began pruning, picked that grapes from and selection, weighed, squeezed, standardized (pH = 3.5, SS = 25%), inoculation (cube foot 10%), fermentation (5 days, T = 30ºC), disc be, malolactic fermentation (45 days), overturned, clarified (Biopectinasa = 0.02%), filtered, packed and stored. The wine has following characteristics: Soluble solids = 7.5%, alcoholic grade = 14.4 GL, pH = 3.29, tabulable acidity = 1.190%, volatile acidity = 0.032%, fixed acidity = 1.061 %, density = 0.987 g/ml, total dried extract = 3.5%, reducer sugars = 1.90%, total Sulphur us = 320 mg/I, free Sulphur us = 120 mg/I, stored during 3 months’ in atmosphere temperature (27°C) that has shown stability and microbiological quality.